Virtuosity - Martinez, Jessica (New York : Simon Pulse, 2011)
Just before the most important violin competition of her career, seventeen-year-old prodigy Carmen faces critical decisions about her anti-anxiety drug addiction, her controlling mother, and a potential romance with her most talented rival.
Keywords: Violin -- Fiction; Musicians -- Fiction; Mothers and daughters -- Fiction; Competition (Psychology) -- Fiction; Conduct of life -- Fiction; Drug abuse -- Fiction; Chicago (Ill.) -- Fiction; Violin -- Fiction; Musicians -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Competition (Psychology) -- Juvenile fiction; Conduct of life -- Juvenile fiction; Drug abuse -- Juvenile fiction; Chicago (Ill.) -- Juvenile fiction